Implementing cultural heritage conservation and energy sustainability in the UNESCO World Heritage site of Jaipur city, India - Bhati, Harsh Vardhan (Frontiers in Sustainable Cities, 2025)
World Heritage cities face the complex challenges of balancing cultural heritage protection with the UN Sustainable Development Goals, particularly reducing greenhouse gas emissions and achieving energy sustainability. However, implementing these commitments at the local level often presents challenges. Using the walled city of Jaipur, a UNESCO World Heritage site in India, as a case study, this article examines the impacts, opportunities, and challenges in implementing and applying international and national obligations to preserve cultural heritage in light of obligations to reduce energy use and greenhouse gas emissions in historic urban areas. This article is based on legal research, as well as 9 semi-structured interviews, which include one group interview with three municipal representatives and individual interviews with one state representative, five heritage professionals and consultants, and two heritage property owners. The results show that World Heritage status has enhanced cultural heritage protection while allowing measures toward energy sustainability. Traditional architectural practices, such as the passive climate design of havelis, are already energy efficient, while interventions, such as the integration of solar panels and adaptive re-use of havelis, demonstrate compatibility between heritage conservation and sustainability goals. However, there continue to be challenges, including limited expertise, capacity, and financial resources, while governance inefficiencies, commercialization pressures, inadequate support for residents, and limited community engagement further hinder progress. The study recommends strengthening the governance framework and enforcement mechanisms, providing targeted financial and technological support, and fostering inclusive collaboration and education among these actors to align heritage conservation with energy sustainability at the local level.